2021
DOI: 10.1007/s00277-021-04601-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CD22 expression and expansion of a CD22dim subpopulation in adults with relapsed/refractory B-lymphoblastic leukaemia after treatment with Inotuzumab-Ozogamicin

Abstract: Treatment options for relapsed or refractory B-lymphoblastic leukaemia (r/r B-ALL) are limited and the prognosis of these patients remains dismal, but novel immunotherapeutic options such as the anti-CD22 antibody–drug-conjugate Inotuzumab-Ozogamicin (InO) have improved outcomes in these patients. Flow cytometry is essential to assess antigen-expression prior to treatment initiation of antigen-directed immunotherapies. Here, we present flow cytometric and clinical data of three adult patients with r/r B-ALL wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…15 Furthermore, response in a CD22-negative patient was also described in a case report. 37 Thus, INO might be active in CD22-negative patients and/or those with very dim CD22 [40][41][42] In our cohort, VOD/SOS occurred in only three patients, including one after allogeneic HSCT, although up to four INO cycles were administered prior to transplantation. These data compare favorably to previously reported data.…”
Section: Discussionmentioning
confidence: 74%
“…15 Furthermore, response in a CD22-negative patient was also described in a case report. 37 Thus, INO might be active in CD22-negative patients and/or those with very dim CD22 [40][41][42] In our cohort, VOD/SOS occurred in only three patients, including one after allogeneic HSCT, although up to four INO cycles were administered prior to transplantation. These data compare favorably to previously reported data.…”
Section: Discussionmentioning
confidence: 74%
“… 15 Furthermore, response in a CD22-negative patient was also described in a case report. 37 Thus, INO might be active in CD22-negative patients and/or those with very dim CD22 expression, but this remains to be elucidated in larger studies. Recent data from the INO-VATE trial suggest that patients with high (≥90%) CD22 expression levels had a higher CR rate compared to those with <90% expression (42.1% [n=45/107] vs .…”
Section: Discussionmentioning
confidence: 98%
“…Resistance to CD20-targeted therapies encompasses a spectrum of mechanisms, ranging from alterations in CD20 antigen levels to compromised immune system effector functions, and extending to diverse mechanisms of immune evasion (Figure 4). One of the main causes of resistance is the loss of the CD20 antigen on the surface of the target cell, which can be caused by changes in the expression of the MS4A1 gene, including silenced expression and alternative splicing Frontiers in Immunology frontiersin.org 10 (28,(155)(156)(157)(158). A recent study has shown that the gene encoding CD20 in both healthy and malignant B cells is alternatively spliced into four 5'-UTRs variants, of which especially variants V3 and V4 support robust translation.…”
Section: Resistance To Cd20directed Immunotherapiesmentioning
confidence: 99%